Packet‐Reduced Ranging Method with Superresolution TOA Estimation Algorithm for Chirp‐Based RTLS - Oh, Daegun; Go, Seungryeol; Chong, Jong‐wha (ETRI journal, 2013)
In this paper, a packet‐reduced ranging method using a superresolution time of arrival estimation algorithm for a chirp‐based real‐time locating system is presented. A variety of ranging methods, such as symmetric double‐sided two‐way ranging (SDS‐TWR), have been proposed to remove the time drift due to the frequency offset using extra ranging packets. Our proposed method can perform robust ranging against the frequency offset using only two ranging packets while maintaining almost the same ranging accuracy as them. To verify the effectiveness of our proposed algorithm, the error performance of our proposed ranging method is analyzed and compared with others. The total ranging performance of TWR, SDS‐TWR, and our proposed TWR are analyzed and verified through simulations in additive white Gaussian noise and multipath channels in the presence of the frequency offset.